2017
DOI: 10.2196/jmir.7639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Website That Presents Patients’ Experiences on Self-Efficacy and Patient Competence of Colorectal Cancer Patients: Web-Based Randomized Controlled Trial

Abstract: BackgroundPatients often seek other patients’ experiences with the disease. The Internet provides a wide range of opportunities to share and learn about other people’s health and illness experiences via blogs or patient-initiated online discussion groups. There also exists a range of medical information devices that include experiential patient information. However, there are serious concerns about the use of such experiential information because narratives of others may be powerful and pervasive tools that ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 53 publications
0
56
0
1
Order By: Relevance
“…In fact, in several cases, e.g. [17], evidences do not support the hypothesis that ICT tools used can indeed increase self-efficacy for comping with cancer mainly because of methodological reasons. Those surveys highlight the need for an integrated platform, developed based on a sound methodology, supporting the integration between the patients and health providers, focusing on patient empowerment, offering clinically validated information and support, and highlight the need for evaluation of the developed technologies.…”
Section: Related Workmentioning
confidence: 93%
“…In fact, in several cases, e.g. [17], evidences do not support the hypothesis that ICT tools used can indeed increase self-efficacy for comping with cancer mainly because of methodological reasons. Those surveys highlight the need for an integrated platform, developed based on a sound methodology, supporting the integration between the patients and health providers, focusing on patient empowerment, offering clinically validated information and support, and highlight the need for evaluation of the developed technologies.…”
Section: Related Workmentioning
confidence: 93%
“…Although the PCQ-57 has been used as an outcome in several intervention studies [ 31 33 ], albeit showing no effect, however, information on its construct validity and reliability has never again been provided since the initial study that had reported acceptable to good internal consistencies for its scales and small to medium correlations with global health status as an indicator of quality of life [ 23 ]. In addition, the relationship of PC with conceptually related constructs and potential psychosocial cancer outcomes has not been examined thus far.…”
Section: Introductionmentioning
confidence: 99%
“…krankheitserfahrungen.de). Die Evaluation bisheriger Themenbereiche der Web site www.krankheitserfahrungen.de zeigt, dass die präsentierte Information als Zugewinn zu bestehenden Informationsangeboten empfunden wird [13][14][15].…”
Section: Krankheitsnarrativeunclassified